Effect of Cu and Si Wafer Substrates in Increasing Raman Signal Of Surface-Enhanced Raman Scattering-Based Au Nanoparticles - Hidayah, Affi; Triyono, Djoko; Herbani, Yuliati; Saleh, Rosari (Malaysian Journal of Science, 2025)
Surface-enhanced Raman spectroscopy (SERS) has attracted considerable research interest over the last four decades because of its rapid vibrational spectroscopic detection, high sensitivity, and nondestructive technique for enhancing the generally weak signal from Raman scattering. Here, SERS substrates were fabricated by drop-casting Au nanoparticles (NPs) onto two substrates (Cu and Si wafers). The AuNPs (diameter = 7.3 nm) were synthesized from an Au metal ion solution with a concentration of 4.22 × 10−4 M via photochemical reduction using a femtosecond laser. The SERS substrates were tested for their ability to enhance the Raman signal of paraquat pesticides at 10 ppm. Six vibration peaks of the paraquat pesticides at 671, 838, 1187, 1294, 1530, and 1643 cm−1 were successfully detected and enhanced. The results showed that the SERS substrate on the Si wafer increased the Raman signal more than the Cu wafer.